Structural-functional analysis of modified kudzu starch as a novel instant powder: Role of modified technology - Ruidi He; Chuanlai Du; Songnan Li; Li Guo; Kaiyue Wang; Liping Yang (Food Chemistry: X)
Adopting effective methods to modify starch structure for enhanced functional properties has become a pivotal pursuit within the realm of food science. This study investigated the physicochemical and structural properties of ball milling-modified kudzu starch (BS), extrusion puffing-modified kudzu starch (ES), alcohol-alkali-modified kudzu starch (ANS), urea-alkali-modified kudzu starch (UNS), pullulanase-modified kudzu starch (PS), and extrusion puffing-pullulanase-modified kudzu starch (EPS). The d (0.5) value increasing from 10.54 μm (NS) to 83.99 μm (ANS). The Small-angle X-ray scattering (SAXS) characteristic curve of other modified kudzu starch disappeared except for the UNS. The solubility of EPS was the highest, ranging from 73 % to 80 %, significantly higher than that of NS (0 %–1 %). The agglomeration rates of ES and EPS were 0.3 % and 0.6 %, respectively, at a stirring time of 30 s. indicating favorable hydration properties. Flavonoids content in ES increased to 0.1825 mg/g. Moreover, the resistant starch content of modified kudzu starch was increased, ranging from 58.50 %–86.87 %. This study is expected to provide a scientific foundation for selecting optimal modification methods for the production of instant kudzu powder.